Intramolecular electrochemical dehydrogenative N–N bond formation for the synthesis of 1, 2, 4-triazolo[1, 5-a]pyridines. Issue 15 (22nd July 2019) - Li, Yong; Ye, Zenghui; Chen, Na; Chen, Zhenkun; Zhang, Fengzhi
Abstract : A reagent-free electrochemical synthesis of valuable 1, 2, 4-triazolo[1, 5- a ]pyridines was developed with the N–N bond formation as the key step. Abstract : A metal- and oxidant-free intramolecular dehydrogenative N–N bond formation has been developed under mild and scalable electrolytic conditions. Various valuable 1, 2, 4-triazolo[1, 5- a ]pyridines were synthesized efficiently from the readily available N -(2-pyridyl)amidines. The reactions were conducted in a simple undivided cell under constant current conditions with n Bu4 NBr as both the redox mediator and the electrolyte. This protocol was applied to the efficient synthesis of key intermediates for anti-diabetic compounds.